Outsourcing property management perspective : universities in the District of Perak Tengah / Nurul Sahida Fauzi ... [et al.] - Nurul Sahida, Fauzi; Noratikah, Kamarudin; Siti Nadiah, Mohd Ali; Nor Aini, Salleh; Noraini, Johari (2015)
Outsourcing is the most popular property management practice especially when the management demanded a portion of skilled labor. Generally, the scope of the outsource property management differs from one organization to another. Due to that, sometimes none of these areas hit the desired objectives of outsourcing since they are absent of clear policies by the organization. Furthermore there is lack of awareness on the existence of these entities. The study on outsource property management perspective in universities have never been discussed. This discrepancy needs to be addressed as universities are the starting place to inculcate this awareness since the services provided will indirectly affect the students and staff performances. Thus, this study is carried out (1) to identify the types of outsource property management used by universities in the district of Perak Tengah (Universiti Teknologi Mara, UiTM (Perak) and Universiti Teknologi Petronas, UTP), (2) to gauge the extent of awareness among the students and staff towards the services provided; and (3) to measure the level of satisfaction amongst the respondents on the services provided. This study hopes to contribute towards the awareness of the existence of property management outsourcing and to improve the quality and sustainability of the property management profession. The quantitative method of data collection is used in this study. Structured questionnaires were randomly distributed among students and staff of both universities. Data from the questionnaire was analysed using the SPSS software. The results revealed that 63% of the respondents are aware of the existence of property management outsourcing in their area while 38% are not. Mean analysis showed most of the respondents are satisfied with the services provided where the mean score achieved lies within the range of (3.50 ≤ value ˂ 4.50). This implies that even though they are not aware of the existence of property management outsourcing in their area, they still scored a high level of satisfaction with the services provided.